2007
DOI: 10.1038/sj.onc.1210516
|View full text |Cite
|
Sign up to set email alerts
|

p21Waf1/Cip1/Sdi1 mediates retinoblastoma protein degradation

Abstract: Damage-induced G1 checkpoint in mammalian cells involves upregulation of p53, which activates transcription of p21Waf1 (CDKN1A). Inhibition of cyclin-dependent kinase (CDK)2 and CDK4/6 by p21 leads to dephosphorylation and activation of Rb. We now show that ectopic p21 expression in human HT1080 fibrosarcoma cells causes not only dephosphorylation but also depletion of Rb; this effect was p53-independent and susceptible to a proteasome inhibitor. CDK inhibitor p27 (CDKN1B) also caused Rb dephosphorylation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 20 publications
(30 reference statements)
4
59
0
Order By: Relevance
“…Moreover, the induction of senescence in TACC3-depleted cells was associated with a rapid decrease of the retinoblastoma protein (pRb) (Supplementary Figure 3b). Inhibition of pRb is a typical event during progression of senescence and has been reported to be mediated by elevated levels of p21 WAF that promote pRb degradation in response to DNA damage (Broude et al, 2007). Another noticeable feature of TACC3-depleted MCF-7 cells was the strong increase of HP1g (phospho-Ser83)-positive SAHF in addition to an abundant expression of nuclear p21 WAF (Supplementary Figure 4).…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the induction of senescence in TACC3-depleted cells was associated with a rapid decrease of the retinoblastoma protein (pRb) (Supplementary Figure 3b). Inhibition of pRb is a typical event during progression of senescence and has been reported to be mediated by elevated levels of p21 WAF that promote pRb degradation in response to DNA damage (Broude et al, 2007). Another noticeable feature of TACC3-depleted MCF-7 cells was the strong increase of HP1g (phospho-Ser83)-positive SAHF in addition to an abundant expression of nuclear p21 WAF (Supplementary Figure 4).…”
Section: Resultsmentioning
confidence: 96%
“…S1A). Next, we determined whether the effect of hypoxia requires the p53 function by using parental HT-p21-9 and HT-p21-9-GSE56 cells, which lack functional p53 (21,43,44). As expected, in HT-p21-9-GSE56 cells, IPTG-induced senescence was preventable by rapamycin but not by nutlin-3a (21) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HT-p21-9 cells, derived from HT1080 human fibrosarcoma cells (American Type Culture Collection), provided by Igor Roninson (University of South Carolina, Charleston, SC), were previously described (1,2,7,8). HT-p21-9-GSE56 cells, which lack transcriptional function of p53, were described previously (21,43,44). HT-p21-9 cells were cultured in highglucose DMEM without pyruvate supplemented with FC2 serum (HyClone FetalClone II; Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Next, we investigated the effect of U0126 on cyclin D1 in p16-induced senescence in the HT-p16 cell line, in which IPTG stimulated irreversible senescence by inducing p16. 50 We have previously observed that IPTG-induced cyclins D1 and E in HT-p16 cells.…”
Section: Resultsmentioning
confidence: 99%